From Fishing to Tourism: A New Generation of Fishermen and Marine Resource Tourism in Indonesia - Lucky Zamzami; Akifumi Iwabuchi (Andalas International Journal of Socio-Humanities, 2019)
This paper explains about fishermen community on the West Sumatra related to the state of tourism resources. A higher pressure economic situation on the coast made the fishermen community turn to tourism activity. The fishermen community has involved in tourism area who have been fishing for much longer. Fishermen households included the new generation of the fishermen have also diversified their incomes, with many fishing households turning to tourism actors with men and women involved in various activities in the tourism area. This research used a qualitative approach with the descriptive-interpretative method. Data of research were taken from several fishermen households directly related to the tourism area in the village of Sungai Pisang, Bungus Teluk Kabung District, Padang. This paper discusses fishermen community as the new fishermen, mainly of the village of Sungai Pisang population group, has often been blamed for the loss of traditional access regulations by the effect of marine resource tourism. Fishermen community and their identity with related to this employment generation for marine resource tourism. Development of marine resource tourism brings their life changes of the fishermen's families, in the form of socio-cultural and economic changed.